pH as a Primary Control in Environmental Microbiology: 2. Kinetic Perspective - Jin, Qusheng; Kirk, Matthew F. (Frontiers in Environmental Science, 2018)
In a companion paper, we examined the thermodynamic responses of microbial redox reactions to pH changes. Here we explore how these thermodynamic responses may affect the composition and function of microbial communities. We simulate butyrate syntrophic oxidation, sulfate reduction, and methanogenesis by microbial consortia at pH ranging from 7 to 5. The simulation accounts for the thermodynamics of microbial metabolisms and the interactions among microbes. The results show that thermodynamic responses to variation in pH can be strong enough to speed up or slow down microbial metabolisms. These kinetic changes then shape the outcome of microbial interactions, including the membership and activity of microbial consortia. Moreover, the kinetic changes modulate carbon fluxes and the efficiency of methane production. The simulation results support the hypothesis that environmental pH can shape the composition and metabolic function of microbial communities by changing the energy yields of redox reactions. They also add to the current theories of microbial ecology. Specifically, due to pH-induced thermodynamic responses, the principle of competitive exclusion fails for microbial processes with significant thermodynamic limitations, which allows the co-occurrence of competing respiration reactions in natural environments. Taken together, these results confirm that pH is a primary control in environmental microbiology. They also highlight the feasibility and potential of biogeochemical kinetic modeling in uncovering and illuminating mechanistic relationships between environmental parameters and microbial communities.